2022
DOI: 10.1136/bmjopen-2021-054650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of routinely assessing and addressing depression and diabetes distress on clinical outcomes among adults with type 2 diabetes: a systematic review

Abstract: ObjectivesThis study examined the effect of using patient-reported outcome measures (PROMs) routinely to assess and address depressive symptoms and diabetes distress among adults with type 2 diabetes.DesignA systematic review of published peer-reviewed studies.Data sourcesMedline, Embase, CINAHL Complete, PsycINFO, The Cochrane Library and Cochrane Central Register of Controlled Trials were searched.Eligibility criteriaStudies including adults with type 2 diabetes, published in English, from the inception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…This finding is consistent with a recent survey of U.K. general practitioners, where PROMs are most frequently completed in general practice on paper during a clinical consultation [21]. Our systematic review also suggests that PROM assessment of diabetes distress and depressive symptoms is most frequently undertaken face-to-face, and that pre-consultation completion of PROMs is rare [15,29]. A decade ago, the MIND-2 study demonstrated that emotional health assessment (completed pre-consultation via computer) led to improvements in general emotional well-being and diabetes distress [12], while the Australian TrueBlue study showed similar benefits for reducing depressive symptoms using a nurse-led model of collaborative care [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with a recent survey of U.K. general practitioners, where PROMs are most frequently completed in general practice on paper during a clinical consultation [21]. Our systematic review also suggests that PROM assessment of diabetes distress and depressive symptoms is most frequently undertaken face-to-face, and that pre-consultation completion of PROMs is rare [15,29]. A decade ago, the MIND-2 study demonstrated that emotional health assessment (completed pre-consultation via computer) led to improvements in general emotional well-being and diabetes distress [12], while the Australian TrueBlue study showed similar benefits for reducing depressive symptoms using a nurse-led model of collaborative care [19].…”
Section: Discussionsupporting
confidence: 91%
“…A recent systematic review of PROM use in diabetes care, found studies are sparse in which PROMs are used to assess and address diabetes distress during routine clinical care of adults with type 2 diabetes. [15] Despite guideline recommendations, the international Diabetes Attitudes, Wishes and Needs second (DAWN-2) study found that only a third of people with diabetes (from 17 countries) recall a healthcare professional asking about emotional issues in the previous 12 months [16]. Additionally, 60% of healthcare professionals reported addressing emotional aspects of diabetes only if the person with diabetes initiated such a discussion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Various health care professionals working with people with diabetes may contribute to psychosocial care in different ways based on training, experience, need, and availability (313,326,327). Ideally, qualified mental health professionals with specialized training and experience in diabetes should be integrated with or provide collaborative care as part of diabetes care teams (328)(329)(330)(331), or referrals for in-depth assessment and treatment for psychosocial concerns should be made to such mental health professionals when indicated (314,332,333). A systematic review and meta-analysis showed that psychosocial interventions modestly but significantly improved A1C (standardized mean difference -0.29%) and mental health outcomes (334).…”
Section: Supporting Positive Health Behaviorsmentioning
confidence: 99%
“…While these recommendations exist, studies reporting implementation of diabetes specific measures in routine type 2 diabetes in general practice are scare. (7) Guideline recommendations to include emotional health assessment during diabetes care are consistent with the generalist model of care. (8) However, several studies indicate that these guidelines are not translating into practice.…”
Section: Introductionmentioning
confidence: 99%
“…To support future use of any PROM collection and use in the clinical consultation, there are both patient, healthcare profession and environmental barriers that need to be addressed. (33) Systematic review evidence suggests that studies of collection and use of diabetes distress and depressive PROMs in diabetes care are scarce, PROM implementation in diabetes care requires further exploration (7).…”
mentioning
confidence: 99%